Odpowiedzi

2009-11-30T15:47:57+01:00
5x+3y=0
-x-2y=7

5x+3y=0
-5x-10y=35
-7y=35
y=-5
2009-11-30T15:51:27+01:00
5x + 3y = 0
-x-2y = 7 /*5

5x+3y=0
-5x-10y=35

5x+3y+-5x-10y=35
5x+3y=0

-7y=35 / : (-7)
5x+3y=0

y= -5
5x+3*(-5)=0

y = -5
5x - 15 = 0 / +15

y = -5
5x = 15 / :5

y= -5
x= 3



2009-11-30T16:04:32+01:00
5x+3y=0
-x-2y=7 / ×5

5x+3y=0
-5x-10y=35

(5x z -5x się redukuje)

-7y=35 /÷ (-7)
y=-5

aby wyliczyć x trzeba podstawić pod równanie

5x+3×(-5)=0
5x-15=0
5x=0+15
5x=15 /÷5
x=3

y=-5
x=3